Progressive Policy Innovation in a Conservative Context? Factors Influencing the Creation of the Non-Discrimination Office in Providencia (Revista Iberoamericana de Estudios Municipales, 2025)
This research examines the factors that influence municipal innovation in addressing public issues of a moral nature, focusing on the creation of the Office of Non-Discrimination and Diversity in Providencia in 2013. Through semi-structured interviews and document reviews, eight factors were identified that can either facilitate or hinder innovation, depending on the institutional context. The findings indicate that political leadership, financial capacity, values, and a favorable public opinion climate — by reducing the political costs associated with promoting polarizing initiatives — were crucial to implementation. Therefore, the sustainability of local innovations in moral policies is closely linked to electoral volatility and the prevailing ideologies of the authorities.
Keywords: municipalities; innovation; moral policing; diversity; LGBTQIA